The employer of last resort scheme and the energy transition: A stock-flow consistent analysis - Giuliano Toshiro Yajima (Levy Economics Institute of Bard College, 2021)
The health and economic crises of 2020-21 have revived the debate on fiscal policy as a major tool for stabilization and meeting long-term goals. The massive surge in unemployment, due to the economic disruption of the lockdown measures, has increased the interest in policies that target employment directly instead of trying to achieve it via a general "demand push." One of the proposals currently under debate is the job guarantee. Under such a policy the government would act as an "employer of last resort" by offering a job to everyone that is able and wants to work but cannot find a job in the private sector. This paper argues that a carefully designed scheme of direct employment and public provision by the state - addressing both the low- and high-skill workforce - can have permanent effects and promote the economy's structural transformation, in particular by fostering energy transition and a lower carbon footprint. Starting from this point, a stock-flow consistent model is developed to study the long-run effect of the job guarantee's implementation, inspired by the work of Godin (2013) and Sawyer and Passarella (2021).
Keywords: B52; J68; Q43; 330; Stock-Flow Consistent Models; Job Guarantee; Structural Change; EnergyTransition